ANKSI KEBIRI KIMIA BSAGI PELAKU KEJAHATAN SEKSUAL TERHADAP ANAK - Friandy, Bob (IAIN Langsa, 2017)
Sexual crime case against children???s in Indonesia are increasing rapidly from time to time. The more tragic fact is that most of the suspect origins from their own kin or around the neighborhood, such as family, school officer, and their playmates sphere. According to Indonesian Child Protection Commision (KPAI), there are 2,275 cases occurred on 2011, 887 amongs them are sexual crime case with violent against children. The protection law towards children vastly consist of criminal law aspect, legal law aspect, material-formal law aspect, state administration law aspect, and of course, the legal law aspect. Sexual abuse against children are criminal case which has been coded in criminal law in Indonesia and also viewed theoritically from Islamic criminal law. Therefore, this Thesis is researching about how are the criminal sex cases againts children viewed from criminal law in Indonesia and Islamic criminal law aspect? And also how is the analysis of Law No. 35/ 2014 (Undang-Undang Nomor 35 Tahun 2014) concerning chemichal castration sanction viewed from Islamic Criminal Law? This research categorized as normative law research which pointing to laws and criminal law principal in Indonesia and also Islamic criminal law. This research using comparative-analysis-descriptive method which describe systematically the fact about cases by comparing the research description. This research compare the Indonesian criminal laws principal and Islamic criminal law principal, criminal law formula and Islamic criminal law formula, and also the rules about the chemichal castration sanction to the convicted sex crime againts children in Indonesian criminal law and Islamic criminal law. This research also analize the law no. 33/2014 concerning the sanction specially?  on the implementation of the law in society. Exclusive study on the Islamic criminal law theory concerning the goverment step on applying the rule, are also executed. There are two points earn from this reearch; the first one is sex crime against children is special crime case. The sanction of the violation arranged in the law no.35/2014 about child protection. In Islamic criminal law (fiqh jinayah) the chemichal castration sanction againts children is in form of jarimah ta???zir. Secondly, in the law no. 35/ 2014 about child protection consist the criminal law aspect, the urgent application about the law is the penal policy which include the protection for the child as the sex crime victim, law enforcement, and justice. The solution for the victim by using Restorative Justice concern measure and the effect againts children as the sexual crime victim. In non penal policy by the role of the parents, family, society, goverment, and the country, on their obligation to protect the child. Chemichal castration sanction studied in Islamic criminal law to give contribution needed by Islamic Law and inline with the principal of Islamic criminal law, especially to preserve the heredity (hifzu- nasli).